2000
DOI: 10.1046/j.1365-2826.2000.00428.x
|View full text |Cite
|
Sign up to set email alerts
|

Prolactin‐Releasing Peptide is Expressed in Afferents to the Endocrine Hypothalamus, but not in Neurosecretory Neurones

Abstract: Prolactin release from the anterior pituitary is regulated principally by inhibitory influences imparted by the tuberoinfundibular dopamine system. Stimulatory control is provided by several hypothalamic, peripheral and local factors. Recently a new peptide, prolactin releasing peptide (PrRP), showing prolactin-secretagogue effects was discovered, synthesized and found to be expressed in brain. We have used histochemical and axonal transport methods to characterize the distribution of PrRP mRNA in the rat brai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
45
0
1

Year Published

2001
2001
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(50 citation statements)
references
References 66 publications
4
45
0
1
Order By: Relevance
“…This is the site where recognized releasing and inhibiting factors of hypothalamic origin gain access to the hypophysial portal vasculature and the anterior lobe. Instead, PrRP immunoreactive neurons in medulla have been identified by retrograde labeling to project to the paraventricular nucleus of the hypothalamus [40]. Furthermore, the number of PrRP neurons does not differ in the medulla of brains from male, nonpregnant female and pregnant female rats [40], and the distribution of PrRP immunoreactive fibers does not change during the estrous cycle [31].…”
Section: Novel Methodology Reenergizes the Hunt For The Missing Prfmentioning
confidence: 99%
See 3 more Smart Citations
“…This is the site where recognized releasing and inhibiting factors of hypothalamic origin gain access to the hypophysial portal vasculature and the anterior lobe. Instead, PrRP immunoreactive neurons in medulla have been identified by retrograde labeling to project to the paraventricular nucleus of the hypothalamus [40]. Furthermore, the number of PrRP neurons does not differ in the medulla of brains from male, nonpregnant female and pregnant female rats [40], and the distribution of PrRP immunoreactive fibers does not change during the estrous cycle [31].…”
Section: Novel Methodology Reenergizes the Hunt For The Missing Prfmentioning
confidence: 99%
“…Instead, PrRP immunoreactive neurons in medulla have been identified by retrograde labeling to project to the paraventricular nucleus of the hypothalamus [40]. Furthermore, the number of PrRP neurons does not differ in the medulla of brains from male, nonpregnant female and pregnant female rats [40], and the distribution of PrRP immunoreactive fibers does not change during the estrous cycle [31]. Finally, Lawrence and co-workers [42] have reported that expression of PrRP apparently decreases in lactation and fasting, suggesting a role for the peptide related to energy homeostasis and not the neuroendocrine regulation of PRL secretion.…”
Section: Novel Methodology Reenergizes the Hunt For The Missing Prfmentioning
confidence: 99%
See 2 more Smart Citations
“…In the rat brain, PrRP nerve cell bodies are distributed in the hypothalamic dorsomedial nucleus (DMN), the nucleus of the solitary tract (NTS), and ventral and lateral reticular nuclei (VLRN) in the medulla oblongata (3133). PrRP neurons in the VLRN and NTS are considered to be A1 and A2 noradrenergic neurons, respectively (34, 35). PrRP nerve fibers project to several brain regions, such as the bed nucleus of the stria terminalis, hypothalamic paraventricular nucleus (PVN), hypothalamic periventricular nucleus (PerVN), and basolateral amygdaloid complex (31, 36).…”
Section: Distribution Of Prrp Prrp2 and Their Receptorsmentioning
confidence: 99%